Interleukin-18 is a novel mitogen of osteogenic and chondrogenic cells. - Cornish, J; Gillespie, M; Callon, K; Horwood, N; Moseley, J; Reid, I (2003)
IL-18 was identified due to its ability to induce interferon-gamma (IFNgamma) production by T cells. It is a pleiotropic factor that shares structural features with IL-1 and functional activities with IL-12. IL-18 has a role in T cell development, where it has been demonstrated to act cooperatively with IL-12 to regulate IFNgamma. In bone, IL-18 is mainly produced by macrophages, but is also expressed by osteoblasts and inhibits osteoclast formation through granulocyte-macrophage colony-stimulating factor (GM-CSF) and not IFNgamma production by T cells. We have investigated the effects of IL-18 on mature osteoclast activity and for potential actions on osteoblasts or chondrocytes. The effects of IL-18 on mature osteoclast activity were determined using two assays: isolated mature osteoclast cell culture and neonatal murine calvarial organ culture. IL-18 did not affect bone resorption in either assay system. The actions of IL-18 on osteogenic cells (primary cell cultures of fetal rat and neonatal mouse osteoblasts, as well as neonatal mouse calvarial organ culture) and primary chondrocytes (canine) were assessed by proliferation assays (quantification of cell numbers and thymidine incorporation). In each assay system, IL-18 acted as a mitogen to the osteogenic and chondrogenic cells. Since IL-18 signal transduction may involve IFNgamma or GM-CSF, we assessed their involvement in the IL-18 response. IL-18 did not induce IFNgamma production by primary osteoblasts, but, of greater significance, IFNgamma had the opposing action to IL-18 in that it inhibited the primary osteoblast cell proliferation. Although IL-18 rapidly induced GM-CSF production by primary osteoblasts, IL-18 was still mitogenic in osteoblast preparations established from GM-CSF-deficient mice. Combined, these studies indicate that IL-18 may have an autocrine/paracrine mitogen role for both osteogenic and chondrogenic cells, independent of the production of IFNgamma or GM-CSF.